Effects of Purple Corn Anthocyanin on Blood Biochemical Indexes, Ruminal Fluid Fermentation, and Rumen Microbiota in Goats - Tian, Xing-Zhou; Li, Jia-Xuan; Luo, Qing-Yuan; Zhou, Di; Long, Qing-Meng; Wang, Xu; Lu, Qi; Wen, Gui-Lan (Frontiers in Veterinary Science, 2021)
The objective of this study was to observe the effects of anthocyanin from purple corn on blood biochemical indexes, ruminal fluid fermentation parameters, and the microbial population in goats. A total of 18 Qianbei Ma wether kids (body weight, 21.38 ± 1.61 kg; mean ± standard deviation) were randomly assigned to three groups using a completely randomized design. The group diets were: 1) control, basal diet, 2) treatment 1 (LA), basal diet with 0.5-g/d purple corn pigment (PCP), and 3) treatment 2 (HA), basal diet with 1-g/d PCP. The results showed that compared to the control group, the inclusion of anthocyanin-rich PCP led to significantly increased (P < 0.05) plasma reduced glutathione and peroxidase concentrations. Goats receiving PCP had increased (P < 0.05) ruminal fluid acetic acid and a higher ratio of acetate to propionate, while the propionic acid, butyric acid, valeric acid, isobutyric acid, and isovaleric acid levels had decreased (P < 0.05). There was no significant difference (P > 0.05) in ruminal fluid alpha bacterial diversity among the three groups. Compared with the control group, feeding LA increased (P < 0.05) the relative abundance of norank_f_F082, while HA decreased (P < 0.05) the relative abundance of Prevotellaceae_NK3B31_group in the rumen. In addition, significant differences (P < 0.05) were also observed for the ruminal fluid Actinobacteriota, Elusimicrobiota, WPS-2, Cyanobacteria, norank_f_Ruminococcaceae, Eubacterium_ventriosum_group, U29-B03, unclassified_c_Clostridia, Pyramidobacter, Anaeroplasma, UCG-004, Weissella, norank_f_norank_o_norank_c_norank_p_WPS-2,norank_f_norank_o_Kapabacterials, norank_f_norank_o_Gastranaerophilales, Mailhella, Endomicrobium, norank_f_Eggerthellaceae, and unclassified_f_Atopobiaceae among all groups. Moreover, the relative abundance of bacterial communities among the three groups was found to be significantly (P < 0.05) different in multilevel discriminant analysis. A total of 55 biomarkers were obtained, and experimental groups had 52 biomarkers when the linear discriminant analysis (LDA) value was higher than 2.0. Additionally, the highest LDA values of the control, LA, and HA groups were UCG-004, Prevotellaceae_NK3B31_group, and Amnipila; these were the bacteria with the greatest differences in relative abundance. Taken together, the inclusion of anthocyanin-rich PCP increased the antioxidant potential, improved rumen volatile fatty acids, and induced a shift in the structure and relative abundance of ruminal microbiota in growing goats.